Encapsulation improves viability and stability of spray-dried Lactococcus lactis A12 for inclusion in fish feed - Marcelo Fernando Valle Vargas; Ruth Yolanda Ruíz Pardo; Luisa Villamil-Díaz; Jader Alean; Patricio Román Santagapita; María Ximena Quintanilla-Carvajal (PLoS ONE, 2025)
During probiotics manufacturing, drying is a crucial process for stabilization of probiotics after fermentation, since drying condition could affect viability and functionality as well as physical properties such as moisture content and water activity, which play key role in stability of dried probiotics during storage. Therefore, this study aimed to evaluate the effect of spray-drying parameters on the survival of Lactococcus lactis A12 after drying and exposure to gastrointestinal conditions. A combined mixture-process design was carried out by evaluating three factors: whey (10–30% w/v), maltodextrin (10–30% w/v), and atomization pressure (1.0–1.5 bar). As the main results, a high concentration of whey (30% w/v), low concentration of maltodextrin (10% w/v), and high atomization pressure (1.4 bar) improved survival of spray-dried L. lactis A12 after drying and exposure to pH 3.00 or bile salts with survival rates ranged within 69.25 to 86.24%, 65.89–98.93%, and 89.09–100%, respectively. Under optimal conditions, spray-dried probiotic powder with wall materials (encapsulated) exhibited higher glass transition temperature (64.44 vs 12.65 °C), and lower hygroscopicity (12.65 vs 64.44%) than spray-dried probiotic without wall materials (non-encapsulated). Moreover, SD probiotic powder exhibited the highest survival rate (85.88%) at 4 °C during 60 days of storage in comparison to 25 °C and 37 °C which did not survive. Finally, spray-dried L. lactis A12 was included in fish feed and exhibited a survival rate of 80.83% when it was stored at 4 °C after 60 days. It can be concluded that the use of encapsulating materials, particularly whey and maltodextrin, improved the physical and thermal stability of L. lactis A12 powder during drying and storage. Also, the results from the stability of supplemented fish feed suggested that L. lactis A12 could be included in fish feed.